Valuation of Start-Up Entities : A Framework on Methodologies and their Practical Implementation - Sarpal, Shivan (AMC Indian Journal of Entrepreneurship, 2024)
Purpose : There are multifarious methods for undertaking the valuation of start-ups; however, there was a lack of a universally accepted valuation methodology on account of divergent valuation perspectives and conceptual approaches. In light of the need to assess the valuation of start-ups for entrepreneurs, fund investors, and other stakeholders, including venture capitalists and regulators, the purpose of this paper was to analyze various valuation methodologies of startup entities that venture capitalists could implement with a specific focus on the computation of pre-money and post-money valuation. Methodology : The current research explored different methodologies for conducting the valuation of start-up entities to assess their practical implementation using relevant cases. Relying upon multiple case scenarios and hypothetical figures, various metrics proposed by different valuation methods were computed and tested accordingly. Findings : The scrutiny of different valuation frameworks indicated stark variations in the methodologies they followed and the inputs they used. Further, there was a lack of a single valuation methodology that could flawlessly match the input data. Hence, it was considered rational to implement multiple valuation frameworks. Additionally, selecting different methods mostly depended on the particularities of the start-ups under study. Practical Implications : Rebutting the â€œOne Size Fits Allâ€ approach further articulated how and when a specific valuation methodology would be adopted. Originality : This analysis offered some new and useful contextual insights that could generate actionable and compelling responses for entrepreneurs while performing their start-up valuation in India.